Long-term assessment of daily atmospheric nitrogen dioxide in Thailand using satellite observed data - Angsumarn Yimlamaid (2020)
© 2020, Thai Society of Higher Eduation Institutes on Environment. All rights reserved. Nitrogen dioxide (NO2) is one of the major air pollutants playing a key role in tropospheric chemistry and climate change. This study analyzed the long-term trend of daily tropospheric NO2 columns in Thailand from 2007 to 2017 (11 years) retrieved from the SCIAMACHY, GOME-2A, GOME-2B and OMI satellites. The consistency between the satellites (GOME-2A vs. SCIAMACHY, GOME-2A vs. GOME-2B and GOME-2A vs. OMI) were investigated during the overlapped time period. Overall, the results showed a good agreement in seasonal variation. The satellite NO2 data were also compared with ground data including NO2 concentrations from ground monitoring stations and meteorological data (temperature, relative humidity and wind speed) over 6 regions of Thailand (North, Northeast, Central, East, Southwest and Southeast). The comparative analysis between satellites NO2 columns and ground NO2 concentrations presented well correlated results. NO2 data from both satellite and ground measurements had maximum levels in the dry season (November-April) with the peak in March while the minimum levels were mostly observed in the wet season (May-October). Moreover, NO2 generally presents at high levels when relative humidity (RH) levels are low.